Comparison of gross calorific value in biomass between standard test method ISO 18125 and ASTM D5865 - Punkrawee, Wachirapun (Bulletin of Applied Sciences, 2022)
In this study, comparison of gross calorific value between ISO 18125 and ASTM D5865 in five types of biomass, including bagasse (A), sugarcane leaf (B), rubber wood (C), rice husk (D) and coconut shell (E), will be conducted. The results of gross calorific value are as follows: rubber wood > bagasse > sugarcane leaf > rice husk > coconut shell. The interval values of percentage relative standard deviation (%RSD) obtained from both methods are similar which are 0.07 -0.21% and 0.08 - 0.18% for the ASTM D5865 and ISO 18125 method, respectively. For student’s t-test, it was found that tcal < tcritical. Therefore, there is no significant difference between calorific value of biomass sample from both methods at 95% confidence level. Hence, ASTM D5865 method can be applicable to determining gross calorific value in biomass samples.